Influence of radiative heat and mass transfer mechanism in system “water droplet-high-temperature gases” on integral characteristics of liquid evaporation; Thermal Science; Vol. 19, iss. 5 - Glushkov D. O. Dmitry Olegovich (2015, 2015)
Title screen